A Comparative Analysis of Different IV and GMM Estimators of Dynamic Panel Data Models - Harris, Mark; Mátyás, L. (Wiley-Blackwell Publishing Ltd., 2004)
It is well known that the usual procedures for estimating panel data models are inconsistent in the dynamic setting. A large number of consistent estimators however, have been proposed in the literature. This paper provides a survey of the majority of mainstream estimators, which tend to consist of IV and GMM ones. It also considers a newly proposed extension to the promising Wansbeek-Bekker estimator (Harris & Matyas, 2000). To provide guidance to the applied researcher working on micro-datasets, the small sample performance of these estimators is evaluated using a set of Monte Carlo experiments.